2014
DOI: 10.1177/1071100713519599
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medial and Lateral Calcaneal Osteotomies on the Tarsal Tunnel

Abstract: These findings provide surgeons with clinical evidence in support of performing a prophylactic tarsal tunnel release for patients undergoing lateralizing calcaneal osteotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 18 publications
3
51
0
1
Order By: Relevance
“…5) is performed more than 9 mm anterior to line A and overpenetrates on the medial side of the calcaneus. Our ndings also indicate that an anteriorly oriented osteotomy places the artery in greater proximity to the osteotomy line than would be the case with an osteotomy that is directed posteriorly, which is consistent with a report by Bruce et al 20 Consistent with ndings reported by both DiDomenico et al and Greene et al that both the LPA and PTA and their branches could cross the Myerson osteotomy line, 3,15 we found that at least one of the medial calcaneal branches crossed line A in all cases. These observations indicate that the medial calcaneal branches (arteries) are at risk during calcaneal osteotomy.…”
Section: Discussionsupporting
confidence: 93%
“…5) is performed more than 9 mm anterior to line A and overpenetrates on the medial side of the calcaneus. Our ndings also indicate that an anteriorly oriented osteotomy places the artery in greater proximity to the osteotomy line than would be the case with an osteotomy that is directed posteriorly, which is consistent with a report by Bruce et al 20 Consistent with ndings reported by both DiDomenico et al and Greene et al that both the LPA and PTA and their branches could cross the Myerson osteotomy line, 3,15 we found that at least one of the medial calcaneal branches crossed line A in all cases. These observations indicate that the medial calcaneal branches (arteries) are at risk during calcaneal osteotomy.…”
Section: Discussionsupporting
confidence: 93%
“…11 In a cadaveric study using magnetic resonance imaging to assess the volume of the tarsal tunnel under varying amounts of both medial and lateral displacement of a calcaneal osteotomy, Bruce et al discovered a 14% to 21% decrease in tarsal tunnel volume dependent on the amount of shift. 3 The authors also observed a trend toward lower volumes with LCO versus medializing calcaneal osteotomies.…”
Section: Discussionmentioning
confidence: 89%
“…Osteotomies of the calcaneus performed through a lateral approach may increase risk to the medial neurovascular structures through direct injury from penetration of the medial cortex, reduction in tarsal tunnel volume from the resulting shift, or compression from the inferior flexor retinaculum. 2,24 Reports of the latter 2 complications are scarce. In addition, complications involving nerve entrapment would not be expected to be different with MIS vs open techniques.…”
Section: Complicationsmentioning
confidence: 99%